Nyxis rostrocularis, a new genus and species of Paranannopinae Por, 1986 (Copepoda, Harpacticoida) from the Southern Atlantic deep sea - Willen, Elke (Zootaxa, 2009)
The species diversity of Copepoda Harpacticoida at several sampling locations in the Southern Atlantic has been investigated. From the obtained multicorer samples, a new taxon of Paranannopinae Por, 1986, Nyxis rostrocularis gen. nov., sp. nov., has been collected, which is described in the present paper. Specimens of the taxon have been encountered in the Angola Basin (DIVA 1 stations 325 and 346), in the Weddell Sea (ANDEEP station 138) and the Cape Basin (DIVA 1I station 36). Nyxis gen. nov. belongs to the group of paranannopid taxa bearing mouthpart aesthetascs. It can be characterised by several autapomorphies discussed in this paper, but takes up a quite isolated position within the Paranannopinae bearing mouthpart aethetascs.